2016
DOI: 10.3390/e18040124
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Heat Machines Equivalence, Work Extraction beyond Markovianity, and Strong Coupling via Heat Exchangers

Abstract: Various engine types are thermodynamically equivalent in the quantum limit of small "engine action". Our previous derivation of the equivalence is restricted to Markovian heat baths and to implicit classical work repository (e.g., laser light in the semi-classical approximation). In this paper, all the components, baths, batteries, and engines, are explicitly taken into account. To neatly treat non-Markovian dynamics, we use mediating particles that function as a heat exchanger. We find that, on top of the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 86 publications
2
82
0
Order By: Relevance
“…In the equivalence regime these machines still have entirely different dynamics, yet their thermodynamics features are the same. This result was recently extended to the non-Markovian regime where the machine and the bath are strongly coupled [56]. For other studies of coherence in quantum heat engines see [41,[57][58][59].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the equivalence regime these machines still have entirely different dynamics, yet their thermodynamics features are the same. This result was recently extended to the non-Markovian regime where the machine and the bath are strongly coupled [56]. For other studies of coherence in quantum heat engines see [41,[57][58][59].…”
Section: Introductionmentioning
confidence: 82%
“…This is experimentally and theoretically well motivated in a wide range of physical systems in atomic physics. Some studies replace the classical field by a quantum battery (work repository) [36,56,60,76,77]. This is very interesting, and deserves further study.…”
Section: Introductionmentioning
confidence: 99%
“…Purely quantum effects in quantum heat engine were discussed in Refs. [489,490]: stationary, twoand four-stroke quantum Otto engines perform equivalently when the operator norm of the time-evolution operator is much smaller than the Planck constant. This becomes possible for few-level quantum systems.…”
Section: Cyclic Quantum Engines and Quantum Coherence Effectsmentioning
confidence: 99%
“…Furthermore, considering a probabilistic approach towards work extraction, [20] found that the achievement of CE is very unlikely, when considering energy fluctuations in the microregime.Can we design a QHE that operates between genuinely thermal reservoirs and yet achieves a high efficiency 5 ? To answer this, several protocols have been proposed and analyzed [9,11,17,[22][23][24][25][26][27], some showing QHEs that operate at the CE [9, 27, 28]. However, crucial to these results is the definition of work.…”
mentioning
confidence: 99%